2012
DOI: 10.1371/journal.pone.0049938
|View full text |Cite
|
Sign up to set email alerts
|

Status of Emergency Obstetric Care in Six Developing Countries Five Years before the MDG Targets for Maternal and Newborn Health

Abstract: BackgroundEnsuring women have access to good quality Emergency Obstetric Care (EOC) is a key strategy to reducing maternal and newborn deaths. Minimum coverage rates are expected to be 1 Comprehensive (CEOC) and 4 Basic EOC (BEOC) facilities per 500,000 population.Methods and FindingsA cross-sectional survey of 378 health facilities was conducted in Kenya, Malawi, Sierra Leone, Nigeria, Bangladesh and India between 2009 and 2011. This included 160 facilities designated to provide CEOC and 218 designated to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
115
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(134 citation statements)
references
References 30 publications
(62 reference statements)
12
115
2
1
Order By: Relevance
“…Also met need for EmOC was high 94% and C/S (7%) have met the UN recommended levels [7]. The findings in this district are contrary to other studies where deliveries in EmOC are lower (9% -47%) and met need for EmOC is also low (6% -50%) [15,16,19]. This may be explained by the fact that Kilimanjaro region already has high coverage on indicators for reproductive, maternal, newborn and child health compared to other regions or nation level [6].…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Also met need for EmOC was high 94% and C/S (7%) have met the UN recommended levels [7]. The findings in this district are contrary to other studies where deliveries in EmOC are lower (9% -47%) and met need for EmOC is also low (6% -50%) [15,16,19]. This may be explained by the fact that Kilimanjaro region already has high coverage on indicators for reproductive, maternal, newborn and child health compared to other regions or nation level [6].…”
Section: Discussioncontrasting
confidence: 59%
“…Almost all researchers from sub Saharan Africa have also shown this disparity where CEmOC are functioning while BEmOC facilities consistently offer a range of 1-3 signal functions [14][15][16][17][18]. Ameh et al (2012) showed that only 2-6% of BEmOC facilities were fully functional while Oyerinde et al (2011) observed that less than 40% of facilities could offer parenteral anticonvulsants or manual removal of placenta [15,16]. In Hai district only 20% of BEmOC facilities could offer magnesium sulphate, a serious situation given eclampsia & preeclampsia are second leading cause of maternal deaths in Tanzania [1].…”
Section: Discussionmentioning
confidence: 99%
“…The least common EmOC signal function varies from assisted vaginal delivery in Bangladesh 53 to administration of parenteral sedative in Pakistan. 54 However, only 68% of surveyed first-line referral facilities in Afghanistan could perform all basic EmOC signal functions, 55 whereas in India, 36% for private health facilities and 6% of government facilities were EmOC centers, 56 and 13% of public health facilities in Pakistan were basic EmOC facilities.…”
Section: Discussionmentioning
confidence: 99%
“…First, signal functions for assessment of EmNC in this study did not include provision of prophylactic antibiotics to the mother in case of preterm or prolonged premature rupture of membranes, which may limit the ability to compare the findings with other studies. In addition, the number of basic EmONC facilities has fluctuated over the years, 21,32,53,62 possibly due to supply failure or inability to deliver the service (e.g., lack of drugs or absence of a provider, and renovations of maternity wards). Studies that enable a better understanding of this gap will help to guide future preventive interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Although, the total number of facilities for the population was adequate, none of the facilities met the minimum UN coverage rates for EmOC. This shows that health facilities in developing countries do not currently have the capacity to adequately respond to and manage women's obstetric complications 10 . A national study to determine the availability, pattern of utilization and quality of essential obstetric care (EOC) facilities in Nigeria reported that only about a fifth of all the health care facilities met the criteria for EmOC with 4.2 % for public facilities (1.2 % for BEmOC and 3.9 % for CEmOC) and 32.8 % for private facilities (5.3 % for BEmOC and 27.5 % for CEmOC).…”
Section: Introductionmentioning
confidence: 99%